DIGITALISASI PRODUK HALAL DI SENTRA INDUSTRI SUKAREGANG KABUPATEN GARUT PADA MASA COVID 19 - Habib Mumtaz JR (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung, 2021)
Garut is a district in West Java between the main routes connecting Bandung with lakes. With a variety of natural and religious tourism. Garut has special foods such as dodol, various local spices and leather crafts. However, with the spread of the Covid 19 outbreak in Indonesia, this has had a negative impact on the economy of Garut and the potential of the area. Various steps have been taken to restore the health sector and the regional economy affected, such as the implementation of PSBB as well as assistance programs, economic relaxation. So, recovery steps must be taken by adjusting new habits, one of which is the digitization of guaranteed local products such as halal products, where safety be prioritized according to Sharia principles and the economy in the region itself must be restored.Keywords: Digitalization, Garut, PSBB, Halal Products